Revue de la Coopération Internationale : organe officiel de l'Alliance Coopérative Internationale (Londres: ACI)
"Periodiciteit: maandelijksHoofdredactie: H.J. MayRedactie: Victor Serwy, G. Fauquet, A.J. Cleuet, A. Axelsen, Drejer, Jean Gaumont, J.P. Warbasse, Emmy Freundlich, W.P. Watkins, I.M. Schenkman"